Stretchable covalent organic framework material as well as preparation method and application thereof
By introducing stretchable segments into covalent organic framework materials, the problem of rigidity limitation of COFs has been solved, resulting in materials with high stability and stretchability, thus expanding their application in multifunctional devices.
Patent Information
- Application Number
- CN202511002519.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-21
- Publication Date
- 2025-10-28
AI Technical Summary
Most existing covalent organic frameworks (COFs) are rigid and lack flexibility and stretchability, which limits their application in dynamic properties and multifunctional devices.
By introducing stretchable segments between the two frameworks of a covalent organic framework material, a stretchable covalent organic framework material structure is formed, which retains crystallinity and photoelectric properties while possessing higher stretchability.
The stability and stretchability of covalent organic framework materials have been achieved, expanding their applications in fields such as flexible electronic skin, sensors, photovoltaic devices, energy storage devices, and gas adsorption materials.
Smart Images

Figure CN120842564A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of covalent organic framework materials technology, specifically relating to a stretchable covalent organic framework material, its preparation method, and its application. Background Technology
[0002] Covalent organic frameworks (COFs) are a class of extended crystalline organic materials with unique structures, possessing advantages such as high specific surface area and tunable pore size. Furthermore, their structure is designable and their properties are easily tunable. These highly attractive characteristics make COFs promising for applications in adsorption and separation, catalysis, energy storage and conversion, sensing, and drug delivery. The design and synthesis of stretchable COFs for optoelectronic applications provides new materials for stretchable organic optoelectronic devices. Integrating flexibility and stretchability into COFs offers a fascinating pathway for developing advanced materials with dynamic properties and multifunctionality. However, most reported COFs are rigid, and research on developing flexible, stretchable COF frameworks is relatively limited. The main challenge lies in the fact that the highly ordered and periodic arrangement of COF crystals restricts molecular motion to some extent. As a result, only a few flexible COFs have been reported. Many researchers have focused on designing functional flexible, stretchable organic frameworks for stretchable devices. Although some progress has been made, a significant gap remains between stretchability and practical applications. Therefore, providing a novel stretchable organic framework material is essential for the excellent performance and application prospects of organic framework materials. Summary of the Invention
[0003] To address the aforementioned technical problems, this invention provides a stretchable covalent organic framework material, its preparation method, and its application. The two frameworks of the organic framework material are directly connected through stretchable segments to form a stretchable covalent organic framework material structure. This structure retains the crystallinity, optical and electrical properties of the organic framework material while allowing for greater stretchability through the expansion and contraction of the stretchable segments between the frameworks.
[0004] In a first aspect, the present invention provides a stretchable covalent organic framework material, wherein the stretchable covalent organic framework material is formed by connecting organic framework materials through stretchable segments.
[0005] The general structural formula of the stretchable covalent organic framework material is shown below:
[0006]
[0007] in:
[0008] X1 can be any one of S, O, and NH, and X2 can be any one of S, O, and NH. X1 and X2 can be the same.
[0009] Y1 is a functional group -CH2-, Y2 is a functional group -CH=CH2; or Y1 is... Y2 is ;
[0010] R is , , Any structure in the range; n is the degree of polymerization of the stretchable covalent organic framework material, ranging from 10 to 3000;
[0011] * indicates a connection point with other structures, and wavy lines indicate omitted repeating chains X1 or X2.
[0012] In a second aspect, the present invention provides a method for preparing the stretchable covalent organic framework material described in the first aspect, comprising the following steps:
[0013] Step 1) Cyclic organic framework materials A-COFs are prepared from monomers A and C by a solvothermal method. The structural formula of A-COFs is as follows:
[0014]
[0015] Step 2) Cyclic organic framework materials B-COFs are prepared from monomers B and C by a solvothermal method. The structural formula of B-COFs is as follows:
[0016]
[0017] Step 3) Crosslink A-COFs, B-COFs, and monomer D containing stretchable segment R to prepare the stretchable covalent organic framework material.
[0018] Furthermore, monomers A, B, C, and D can be classified into the following groups based on their different functional groups and reaction types:
[0019] (1) Group 1:
[0020] Monomer A and monomer B are independently selected from , , Any one of them;
[0021] Monomer C is ;
[0022] Monomer D is , , Any one of them.
[0023] (2) Second group:
[0024] Monomer A and monomer B are independently selected from , , Any one of them;
[0025] Monomer C is ;
[0026] Monomer D is , , Any one of them.
[0027] (3) Group 3:
[0028] Monomer A and monomer B are ;
[0029] Monomer C is , Any one of them;
[0030] Monomer D is , , Any one of them.
[0031] (4) Group 4:
[0032] Monomer A and monomer B are ;
[0033] Monomer C is , Any one of them;
[0034] Monomer D is , , Any one of them.
[0035] Furthermore, the preparation method includes the following steps:
[0036] Step 1) Dissolve monomers A and C in a solvent and add a catalyst. Sonicate the mixture until the solid is completely dissolved. Cycle the mixture under vacuum three times. Heat the reactants to 120°C using a solvothermal method and react for 3 days. Then cool the mixture to room temperature naturally. Centrifuge and wash the mixture. Dry the solid in an oven to obtain the cyclic organic framework material A-COFs.
[0037] Step 2) Dissolve monomers B and C in a solvent and add a catalyst. Sonicate the mixture until the solid is completely dissolved. Cycle freeze and vacuum three times. Heat the reactants to 120°C for 3 days using a solvothermal method. Then cool naturally to room temperature. Centrifuge and wash the mixture. Dry the solid in an oven to obtain ring-shaped mechanical framework material B-COFs.
[0038] Step 3) Depending on the type of linkage reaction, photocrosslinking and hydrogen bonding crosslinking reactions can be carried out.
[0039] (1) Photocrosslinking reaction: Organic framework materials A-COFs, B-COFs, and monomer D containing stretchable segments R were placed in a solvent and then placed in a mold. A photocrosslinking agent and a photoinitiator were added, and the mold was placed in an ultraviolet crosslinking instrument under 254 nm ultraviolet light for 24 h to obtain a cured COFs film. The film was then washed with DCM, acetone, and deionized water, and dried at 60 °C to obtain the target product. The monomers A, B, C, and D corresponding to the first and third groups above underwent photocrosslinking reactions.
[0040] (2) When performing hydrogen bonding crosslinking reaction: Organic framework materials A-COFs, B-COFs, and monomer D containing stretchable segments R are placed in a solvent, the mixture is placed in a mold, and reacted in an oven at 120°C for 3 days. After the reaction, a cured COFs film is obtained in the mold. The monomers A, B, C, and D corresponding to the second and fourth groups above undergo hydrogen bonding crosslinking reaction.
[0041] In this material, monomers A and C, and monomers B and C form a bicyclic organic framework material through X; monomer C contains a connecting bond Y, and the bicyclic organic framework material is connected to the stretchable chain segment R through the connecting bond Y to form a stretchable covalent organic framework material.
[0042] Furthermore, in step 1), the molar ratio of monomer A to monomer C is 1:1; in step 2), the molar ratio of monomer B to monomer C is 1:1; in step 3), the molar ratio of A-COFs, B-COFs, and monomer D is 1:1:1.
[0043] Furthermore, in steps 1) and 2), the catalyst is one of potassium tert-butoxide, potassium hydroxide, and sodium hydroxide.
[0044] Furthermore, the solvent in steps 1) and 2) is 1,4-dioxane;
[0045] Furthermore, the solvent in step 3) is a mixture of 1,2-dichlorobenzene, n-butanol, and HOAc;
[0046] Furthermore, in step 3), the photoinitiator is one of 1-hydroxy-cyclohexyl-phenyl ketone, benzoin dimethyl ether, and methyl o-benzoylbenzoate;
[0047] Furthermore, in step 3), the crosslinking agent is one of N,N-methylenebisacrylamide, α-ketoglutaric acid, and ethyl 4-dimethylaminobenzoate.
[0048] Furthermore, in steps 1) to 3), the washing solution used for washing is one or more of DMF (dimethylformamide), THT (tetrahydrothiophene), dichloromethane (DCM), acetone, and deionized water.
[0049] Thirdly, the present invention provides the application of the stretchable covalent organic framework material described in the first aspect, which can be used in the preparation of flexible electronic skin, flexible carbon capture devices, portable air purification systems or flexible supercapacitors.
[0050] Beneficial Effects: This invention introduces stretchable segments into covalent organic framework materials, enabling the resulting covalent organic framework material to retain its crystallinity while possessing stability and stretchability through the expansion and contraction of the stretchable segments connecting the frameworks. The stretchable segment-introduced covalent organic framework material prepared by this invention has a novel structure and a unique design strategy, solving the problem that traditional two-dimensional covalent organic framework materials cannot be stretched due to their rigid intralayer structure. The stretchable connected covalent organic framework material prepared by this invention can be widely used in fields such as flexible skin, electronic paper, sensors, photovoltaics, energy storage / gas adsorption, and nanofiltration materials. Attached Figure Description
[0051] Figure 1 The above are PXRD characterization images of the stretchable covalent organic framework materials prepared in Examples 1-3.
[0052] Figure 2 SEM images of the stretchable covalent organic framework materials prepared in Examples 1-2;
[0053] Figure 3 TGA images of the stretchable covalent organic framework materials prepared in Examples 1-3;
[0054] Figure 4 The image shows the stretching curve of the stretchable covalent organic framework material prepared in Example 2. Detailed Implementation
[0055] The technical solution of the present invention will be described in detail below through embodiments, but the scope of protection of the present invention is not limited to the embodiments described. All raw materials used in the following embodiments can be purchased from the market.
[0056] Example 1
[0057] This embodiment provides a method for preparing a stretchable covalent organic framework material.
[0058] Step 1) Weigh monomer A (66.18 mg, 0.20 mmol), monomer C Potassium tert-butoxide (60.64 mg, 0.30 mmol) and potassium tert-butoxide (269.31 mg, 2.4 mmol) were added to a Pyrex flask, followed by 5 mL of 1,4-dioxane. The mixture was stirred and sonicated for 30 min. The mixture was then subjected to three freeze-drying vacuum cycles. The reaction was carried out at 120 °C for 3 days. After the reaction, the product was centrifuged at 10,000 rpm for 6 min and washed three times with acetone, DCM, and deionized water. The product was then dried at 60 °C to obtain a reddish-brown solid powder, which was the target product, designated ATP-Et-COF.
[0059] Step 2) Weigh monomer B (66.18 mg, 0.20 mmol), monomer C Potassium tert-butoxide (60.64 mg, 0.30 mmol) and potassium tert-butoxide (269.31 mg, 2.4 mmol) were added to a Pyrex flask, followed by 5 mL of 1,4-dioxane. The mixture was stirred and sonicated for 30 min. The mixture was then subjected to three freeze-drying vacuum cycles. The reaction was carried out at 120 °C for 3 days. After the reaction, the product was centrifuged at 10,000 rpm for 6 min and washed three times with acetone, DCM, and deionized water. The product was then dried at 60 °C to obtain a black solid powder, which was the target product, designated HTP-Et-COF.
[0060] Step 3) Weigh out the molars in a ratio of 1:1:1 (n is 10-3000), ATP-Et-COF, and HTP-Et-COF were placed in a mixture of 5 mL 1,2-dichlorobenzene, 5 mL n-butanol, and 0.2 mL HOAc. The mixture was placed in a mold, and 1-hydroxy-cyclohexyl-phenyl ketone (0.1% by mass) was added as a photoinitiator, and N,N-methylenebisacrylamide (0.1% by mass) was added as a photocrosslinking agent. The mold was placed in a UV crosslinker and photocrosslinked under 254 nm UV light for 24 h, resulting in a cured COF film in the mold. The film was removed and washed with DCM, acetone, etc., to obtain the target product, designated ATP-EtR1-HTP-COF, with the following structural formula:
[0061] ,
[0062] The yield was approximately 83%, and XRD characterization was as follows. Figure 1 As shown in (a), there is a distinct crystallization peak at around 2°, indicating that the synthesized ATP-EtR1-HTP-COF has good crystallinity; the SEM characterization image of this stretchable covalent organic framework material is shown in Figure (a). Figure 2 As shown in Figure (a), the morphology of the stretchable covalent organic framework film is a dense array of spherical particles. Thermogravimetric analysis characterization of this stretchable segment-connected covalent organic framework material is as follows: Figure 3(a) indicates that it reaches its maximum decomposition temperature at around 423℃.
[0063] The COF film (ATP-EtR1-HTP-COF) prepared in Example 1 showed no significant shift in XRD peak position after being stretched to 50% strain, remained structurally stable after 90 days in air, had a band gap of 2.1 eV, and a conductivity of 1.2 × 10⁻³ S / cm at room temperature, exhibiting good structural stability, optical responsiveness, and electrical conductivity.
[0064] Application: The stretchable covalent organic framework material prepared in Example 1 is used as a stretchable COF material for flexible electronic skin. Specifically, the stretchable covalent organic framework material prepared in Example 1 is dispersed in an elastic polymer matrix, formed into a uniform thin film, and then integrated onto a flexible circuit substrate to construct a biomimetic electronic skin. This electronic skin maintains a stable electrical signal response under repeated bending and stretching (>50% strain) conditions, exhibits good tactile sensing sensitivity, and is suitable for wearable health monitoring devices.
[0065] Example 2
[0066] Step 1) Weigh monomer A (84.13 mg, 0.20 mmol), monomer C Potassium tert-butoxide (84.66 mg, 0.30 mmol) and potassium tert-butoxide (269.31 mg, 2.4 mmol) were added to a Pyrex flask, followed by 5 mL of 1,4-dioxane. The mixture was stirred and sonicated for 30 min. The mixture was then subjected to three freeze-drying vacuum cycles. The reaction was carried out at 120 °C for 3 days. After the reaction, the product was centrifuged at 10,000 rpm for 6 min and washed three times with acetone, DCM, and deionized water. The product was then dried at 60 °C to obtain orange-yellow solid powders, which were the target products, designated as THT-Et-COF.
[0067] Step 2) Weigh monomer B (64.83 mg, 0.20 mmol), monomer C (84.66 mg, 0.30 mmol) and potassium tert-butoxide (269.31 mg, 2.4 mmol) were added to a Pyrex flask, followed by 5 mL of 1,4-dioxane. The mixture was stirred and sonicated for 30 min. The mixture was then subjected to three freeze-drying vacuum cycles. The reaction was carried out at 120 °C for 3 days. After the reaction, the product was centrifuged at 10,000 rpm for 6 min and washed three times with acetone, DCM, and deionized water. The product was then dried at 60 °C to obtain a black solid powder, which was the target product, designated HTP-Et-COF.
[0068] Step 3) Weigh out the molar ratio of 1:1:1. (n is 10-3000), THT-Et-COF, and HTP-Et-COF were placed in a mixture of 5 mL 1,2-dichlorobenzene, 5 mL n-butanol, and 0.2 mL HOAc. The mixture was placed in a mold, and methyl phthaloylbenzoate (0.1% by mass) was added as a photoinitiator, and α-ketoglutaric acid (0.1% by mass) was added as a photocrosslinking agent. The mold was placed in a UV crosslinking instrument and photocrosslinked for 24 h to obtain a cured COF film in the mold. The film was removed and washed with DCM, acetone, etc., to obtain the target product, designated THT-EtR2-HTP-COF. Its structure is shown below:
[0069] ,
[0070] The yield was approximately 87%, and XRD characterization was as follows. Figure 1 As shown in (b), there are significant crystallization peaks, indicating the formation of THT-EtR2-HTP-COF with good crystallinity. The SEM characterization image is shown below. Figure 2 As shown in (b) of the figure. The stretching curve is as follows. Figure 4 As shown, it has a certain tensile strength.
[0071] The COFs thin film prepared in Example 2 showed an initial decomposition temperature of 410℃, a maximum tensile strain of 70%, a BET specific surface area of 1380 m² / g, a UV-Vis absorption edge at 550 nm (band gap of 2.3 eV), and an electrical conductivity of 8.5 × 10⁻⁻⁻⁶. 4 With a strength of S / cm, it possesses excellent thermal stability, stretchability, and photoelectric properties.
[0072] Application: Stretchable COFs materials for gas adsorption and separation. Specifically, the stretchable covalent organic framework material prepared in Example 2 is coated onto the surface of a flexible porous substrate to construct a flexible gas adsorption membrane module. At room temperature and pressure, this material exhibits a CO2 adsorption capacity of 68 cm³ / g and retains its original adsorption capacity after multiple mechanical deformations, demonstrating excellent structural stability and gas selectivity. It is suitable for use in flexible carbon capture devices or portable air purification systems.
[0073] Example 3
[0074] Step 1) Weigh monomer A (84.13 mg, 0.20 mmol), monomer C Potassium tert-butoxide (84.66 mg, 0.30 mmol) and potassium tert-butoxide (269.31 mg, 2.4 mmol) were added to a Pyrex flask, followed by 5 mL of 1,4-dioxane. The mixture was stirred and sonicated for 30 min. The mixture was then subjected to three freeze-drying vacuum cycles. The reaction was carried out at 120 °C for 3 days. After the reaction, the product was centrifuged at 10,000 rpm for 6 min and washed three times with acetone, DCM, and deionized water. The product was then dried at 60 °C to obtain orange-yellow solid powders, which were the target products, designated as THT-Pz-COF.
[0075] Step 2), Monomer B (63.67 mg, 0.20 mmol), monomer C (84.66 mg, 0.30 mmol) and potassium tert-butoxide (269.31 mg, 2.4 mmol) were added to a Pyrex flask, followed by 5 mL of 1,4-dioxane. The mixture was stirred and sonicated for 30 min. The mixture was then frozen under vacuum three times. The reaction was carried out at 120 °C for 3 days. After the reaction, the product was centrifuged at 10,000 rpm for 6 minutes and washed three times with acetone, DCM, and deionized water. The product was then dried at 60 °C to obtain black solid powders, which were the target products, labeled ATP-Pz-COF.
[0076] Step 3) Weigh out the molar ratio of 1:1:1. (n is 10-3000) THT-Pz-COF and ATP-Pz-COF were placed in a mixture of 5 mL 1,2-dichlorobenzene, 5 mL n-butanol, and 0.2 mL HOAc. The mixture was placed in a mold and reacted in an oven at 120°C for 3 days. After the reaction, a cured COF film was obtained in the mold. The film was removed and washed with DCM, acetone, etc., to obtain the target product, designated THT-PzR3-ATP-COF. Its structure is shown below:
[0077] ,
[0078] The yield was approximately 87%, and XRD characterization was as follows. Figure 1 As shown in (c), a distinct crystallization peak at 2° indicates the formation of THT-PzR3-ATP-COF, suggesting good crystallinity. The TGA image is shown below. Figure 3 As shown in (c).
[0079] The COFs film prepared in Example 3 did not suffer structural damage after being immersed in aqueous solution for 72 hours. It retained more than 88% of its capacitance performance when stretched to 30% strain, with a band gap of 1.9 eV. The specific capacitance measured in the three-electrode system was 220 F / g, demonstrating good chemical stability, electrochemical stretchability and photoresponse characteristics.
[0080] Application: Stretchable COFs material for flexible supercapacitors. Specifically, the stretchable covalent organic framework material prepared in Example 3 was coated onto a flexible substrate and assembled into a flexible supercapacitor. When stretched to 1.3 times its original length, its specific capacitance still retained more than 90% of its initial value, and the capacity retention rate reached 94% after 1000 charge-discharge cycles, demonstrating excellent electrochemical stability and mechanical adaptability, making it suitable for flexible energy storage systems.
[0081] As described above, although the invention has been shown and described with reference to specific preferred embodiments, it should not be construed as limiting the invention itself. Various changes in form and detail may be made without departing from the spirit and scope of the invention.
Claims
1. A stretchable covalent organic framework material, characterized in that, The general structural formula of the stretchable covalent organic framework material is shown below: ; in: X1 can be any one of S, O, and NH; X2 can be any one of S, O, or NH; Y1 is a functional group -CH2-, Y2 is a functional group -CH=CH2; or Y1 is... Y2 is , * indicates a connection point with other structures; R is , , Any structure in the formula, where n is the degree of polymerization of the stretchable covalent organic framework material, ranging from 10 to 3000, and * indicates the connection point with other structures.
2. The method for preparing the stretchable covalent organic framework material according to claim 1, characterized in that, Includes the following steps: Step 1) Cyclic organic framework materials A-COFs are prepared from monomers A and C by a solvothermal method. The structural formula of A-COFs is as follows: ; Step 2) Cyclic organic framework materials B-COFs are prepared from monomers B and C by a solvothermal method. The structural formula of B-COFs is as follows: ; Step 3) Crosslink A-COFs, B-COFs, and monomer D containing stretchable segment R to prepare the stretchable covalent organic framework material.
3. The preparation method according to claim 2, characterized in that, Monomer A and monomer B are independently selected from , , Any one of them; Monomer C is ; Monomer D is , , Any one of them.
4. The preparation method according to claim 2, characterized in that, Monomer A and monomer B are independently selected from , , Any one of them; Monomer C is ; Monomer D is , , Any one of them.
5. The preparation method according to claim 2, characterized in that, Monomer A and monomer B are ; Monomer C is , Any one of them; Monomer D is , , Any one of them.
6. The preparation method according to claim 2, characterized in that, Monomer A and monomer B are ; Monomer C is , One of them; Monomer D is , , One of them.
7. The preparation method according to claim 3 or 4, characterized in that, In step 3), A-COFs, B-COFs, and monomer D containing stretchable segments R undergo photocrosslinking reaction.
8. The preparation method according to claim 5 or 6, characterized in that, In step 3), A-COFs, B-COFs, and monomer D containing stretchable segments R undergo hydrogen bonding crosslinking.
9. The preparation method according to claim 2, characterized in that, In step 1), the molar ratio of monomer A to monomer C is 1:1; in step 2), the molar ratio of monomer B to monomer C is 1:1; in step 3), the molar ratio of A-COFs, B-COFs, and monomer D is 1:1:
1.
10. The application of the stretchable covalent organic framework material according to claim 1, characterized in that, The stretchable covalent organic framework material is used in the fabrication of flexible electronic skin, flexible carbon capture devices, portable air purification systems, or flexible supercapacitors.